The Social Identity Change of Little Bee as the Main Character in Chris Cleave‟s The Other Hand - Riska Hendika Rani (Jurnal Bahasa, Sastra, dan Studi Amerika, 2019)
Chris Cleave‟s novel entitled The Other Hand pictures an African refugee‟s life in the United Kingdom and her struggle to survive in the country. As an illegal refugee from Africa who smuggles herself into a tea ship, Little Bee, the refugee, has to stay in the immigration detention center when she arrives in the United Kingdom. She deals with identity issues during her two-year-stay in the immigration detention center. The questions such as „why don‟t British people treat her in a good way‟ and „why do British people get respect and she does not‟ make her want to be treated like a British, which she assumes, being treated nicely in the United Kingdom. Under the paradigm of social identity theory which contains the three stages of identity formation proposed by Henri Tajfel and John Turner, this study attempts to explain Little Bee‟s process of identity formation. Focusing on Little Bee‟s struggle in the United Kingdom as an illegal refugee from Africa, this study analyzes the three stages of identity formation that Little Bee has been through during her social identity transformation, as well as the factors influencing her and her struggle during the process.